Middle-School Teachers' Use and Development of Engineering Subject Matter and Pedagogical Content Knowledge: A Pilot Study - Hynes, Morgan M. (Tufts Archival Research Center, 2005)
A qualifying paper submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in MSTE Education. Abstract: This paper reports on a study of two middle-school math and one middle-school science teacher as they taught an engineering unit. The study investigated the subject matter knowledge and pedagogical content knowledge these teachers used and developed as they taught an engineering unit that used LEGO to teach students the engineering design process through designing and building an assistive device that uses motors, sensors, and is computer controlled. Data collected from teacher interviews and classroom observations revealed the different subject matter and pedagogical content knowledge the teachers used to teach engineering that was new for them. The data revealed how a teacher's knowledge of physics or engineering can impact their teaching. The data also highlighted that the teachers rarely explicitly used their math or science knowledge to make connections to engineering. The study also illustrated examples of engineering pedagogical content knowledge the teachers developed while teaching the engineering unit. One central conclusion drawn from the study is that teachers would benefit from focused opportunities to develop the different specific types of engineering knowledge that they struggle with the most (i.e., physics concepts, mathematics principles, engineering design). The paper includes a literature review that provides a rationale and framework for studying the teaching of middle-school engineering, a description of the methods used, and results and implications of this study.